Life Style Practice and Awareness during Ramadan Fasting in Bangladeshi Diabetic Population - Amin, Mohammod Feroz; Afsana, Faria; Nazneen, Noor E; Pathan, Faruque; Jamil, Syed Noor Afroze Ashraf; Sultana, Syeda Rezina; Hossain, Farhana Meher; Ahmed, Salma; Rehana, Sultana; Ahmed, Nasreen; Afrique, Nagma H; Akhter, Fatema; et al. (BIRDEM Medical Journal, 2016)
Background: Observing fast during Ramadan is obligatory for every healthy adult Muslim and a significant number of diabetic patients observe fast during Ramadan in Bangladesh. The objectives of this study were to find out the life style changes and also to assess the patients awareness during Ramadan fasting. Methods: This non-interventional, cross-sectional study was conducted in the outpatient department of BIRDEM. Total 2272 patients were primarily enrolled but 977 patients fasted at least 15 days or more and fulfilled the inclusion criteria. Results: Mean age of study population was 49.8 ±32 years, mean duration of diabetes 8.15±23 years and 60% were female. HbA1c done within last six months in 46% patients had a mean of 8.2±1%. Out of 977 patients, 29.37% were hypertensive, CKD and IHD were 7.8% and 13.6% respectively. Considering medications 48% were taking oral anti diabetic drug (OAD), 30% were on both OAD and insulin and 22% were only on Insulin. Pre Ramadan counseling was done in only 32% (314) patients though 80.7% (788) patients claimed that they had been particular to doctors appointment, with an average visit of 3.6 times in a year. Among the 977 patients fasted during Ramadan63.3% followed the diet chart as pre Ramadan but 44.7% patients took most of allotted meal at Iftar, while 14% patients took the main meal at Sohur. In pre Ramadan, 69% (691) patients were particular in regular exercise but it came down to 1.7% during Ramadan and 43.4% patients hold most of their daily activities. Regarding medications 1.22% patients missed their anti diabetic drug in preceding month of Ramadan but it raised to 23.4% (229) during Ramadan. Minor hypoglycemia was experienced in 14.32% patients during fasting and nearly half of them (6.8%) later needed physician consultation during Ramadan. Conclusion: More than two third of Muslim diabetic patients observes fast, among them only one third consult with their physicians before Ramadan. Due to lack of proper diabetic education most of them increase their daily calorie intake, miss the dose of drug leading to physical weakness and also some of them develop minor hypoglycemia. Therefore, pre-Ramadan counseling and education is necessary for all diabetics planning for fasting. Birdem Med J 2016; 6(1): 26-31